Factors influencing the prioritization of vaccines by policymakers in low- and middle-income countries: a scoping review - Guillaume, Dominique; Meyer, Diane; Waheed, Dur-e-Nayab; Schlieff, Meike; Muralidharan, Kirthini; Chou, Victoria B; Limaye, Rupali (Health policy and planning, 2023)
Abstract Vaccination decision making in low- and middle-income countries (LMICs) has become increasingly complex, particularly in the context of numerous competing health challenges. LMICs have to make difficult choices on which vaccines to prioritize for introduction while considering a wide range of factors such as disease burden, vaccine impact, vaccine characteristics, financing and health care infrastructures, whilst adapting to each country’s specific contexts. Our scoping review reviewed the factors that influence decision-making among policymakers for the introduction of new vaccines in LMICs. We identified the specific data points that are factored into the decision-making process for new vaccine introduction, whilst also documenting whether there have been any changes in decision-making criteria in new vaccine introduction over the last two decades. A comprehensive database search was conducted using a search strategy consisting of key terms and Medical Subject Headings (MeSH) phrases related to policy, decision-making, vaccine introduction, immunization programmes and LMICs. Articles were screened following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A total of 843 articles were identified, with 34 articles retained after abstract screening, full-text screening and grading with the mixed methods appraisal tool (MMAT). The Burchett framework for new vaccine introduction was used to identify indicators for vaccine-decision making and guided data extraction. Articles in our study represented a diverse range of perspectives and methodologies. Across articles, the importance of the disease, which included disease burden, costs of disease and political prioritization, coupled with economic factors related to vaccine price, affordability and financing were the most common criteria considered for new vaccine introduction. Our review identified two additional criteria in the decision-making process for vaccine introduction that were not included in the Burchett framework: communication and sociocultural considerations. Data from this review can support informed decision-making for vaccine introduction amongst policymakers and stakeholders in LMICs.